The Domestic and Global Origins of Transnational Advocacy: Explaining Lobbying Presence During WTO Ministerial Conferences. (October 2015) - Hanegraaff, Marcel; Braun, Caelesta; De Bièvre, Dirk; Beyers, Jan
This article explains varying levels of transnational advocacy initiated by domestic organized interests. Theoretically, we integrate the constraining and enabling impact of the domestic context with factors related to global opportunity structures. We test our hypotheses with an original data set consisting of all national organized interests that attended the Ministerial Conferences of the World Trade Organization (WTO) in the period 1995 through 2011. Instead of viewing transnational advocacy as a reaction to a lack of domestic political attention and an attempt to compensate for domestic deprivation, our analyses actually show the opposite. Organized interests that originate from democratic, mostly wealthy countries, and that enjoy robust access to domestic resources, are much more responsive to shifts in the global policy agenda. More generally, our analysis of the factors that drive transnational advocacy point at the irrelevance to artificially juxtapose domestic and global explanations.